Predictive Assessment of the Antiviral Properties of Imperata cylindrica against SARS-CoV-2 - Frank Eric Tatsing Foka; Hazel Tumelo Mufhandu (Advances in Virology)
The omicron variant and its sublineages are highly contagious, and they still constitute a global source of concern despite vaccinations. Hospitalizations and mortality rates resulting from infections by these variants of concern are still common. The existing therapeutic alternatives have presented various setbacks such as low potency, poor pharmacokinetic profiles, and drug resistance. The need for alternative therapeutic options cannot be overemphasized. Plants and their phytochemicals present interesting characteristics that make them suitable candidates for the development of antiviral therapeutic agents. This study aimed to investigate the antiviral potential of Imperata cylindrica (I. cylindrica). Specifically, the objective of this study was to identify I. cylindrica phytochemicals that display inhibitory effects against SARS-CoV-2 main protease (Mpro), a highly conserved protein among coronaviruses. Molecular docking and in silico pharmacokinetic assays were used to assess 72 phytocompounds that are found in I. cylindrica as ligands and Mpro (6LU7) as the target. Only eight phytochemicals (bifendate, cylindrene, tabanone, siderin, 5-hydroxy-2-[2-(2-hydroxyphenyl)ethyl]-4H-1-benzopyran-4-one, maritimin, 5-methoxyflavone, and flavone) displayed high binding affinities with Mpro with docking scores ranging from −5.6 kcal/mol to −9.1 kcal/mol. The in silico pharmacokinetic and toxicological assays revealed that tabanone was the best and safest phytochemical for the development of an inhibitory agent against coronavirus main protease. Thus, the study served as a baseline for further in vitro and in vivo assessment of this phytochemical against Mpro of SARS-CoV-2 variants of concern to validate these in silico findings.